2015
DOI: 10.1089/lgbt.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

A Persistent Disparity: Smoking in Rural Sexual and Gender Minorities

Abstract: Purpose Sexual and gender minorities (SGM) smoke cigarettes at higher rates than the general population. Historically, research in SGM health issues was conducted in urban populations and recent population-based studies seldom have sufficient SGM participants to distinguish urban from rural. Given that rural populations also tend to have a smoking disparity, and that many SGM live in rural areas, it is vitally important to understand the intersection of rural residence, SGM identity, and smoking. This study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(37 reference statements)
2
11
0
Order By: Relevance
“…We found that the overall prevalence of current cigarette smoking was higher among sexual minorities (22.5% in LGB adults) as compared to HET adults (15.3%), which is similar to the findings of other studies (Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; Johnson et al, 2016; King et al, 2012; Lee et al, 2009; Max et al, 2016). Justifications for this high prevalence include normative behavior of socializing at bars, to cope with stress, and having friends and family who smoke (Gruskin et al, 2008; Jannat-Khah et al, 2017; Remafedi, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the overall prevalence of current cigarette smoking was higher among sexual minorities (22.5% in LGB adults) as compared to HET adults (15.3%), which is similar to the findings of other studies (Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; Johnson et al, 2016; King et al, 2012; Lee et al, 2009; Max et al, 2016). Justifications for this high prevalence include normative behavior of socializing at bars, to cope with stress, and having friends and family who smoke (Gruskin et al, 2008; Jannat-Khah et al, 2017; Remafedi, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, a systematic review of 42 studies conducted between 1987 and 2007 reported strong associations between LGB status and smoking, with odds ratios (ORs) between 1.5 and 2.5 (Lee et al, 2009). Thus, it has been well documented that sexual minority populations experience significant disparities related to tobacco use (Balsam et al, 2012; Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; King et al, 2012; Lee et al, 2009; Rath et al, 2013). One potential mechanism that explains this disparity is that LGB individuals experience stigma and harassment, discrimination, rejection from family, and even emotional and physical violence (Balsam et al, 2012; Gruskin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…22,23,54 None, however, sought to elucidate associations to minority stress that might be more prominent for sexual minorities in the rural setting. The participants in our study endorsed their own assumption of minority stress, noting both stressors they experienced as sexual minorities in Appalachia and the predominant role that stress played in smoking behaviors, though many did not perceive that tobacco use was higher among LGB persons than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…17–19 Various studies conducted in urban settings have demonstrated high rates of smoking among sexual minority populations in the United States. 3,6,20,21 Smoking prevalence among rural LGB persons is not well established but at least two studies provide evidence that in some areas the proportion of current smokers among LGBT in a rural state or rural areas of a state (45–46%) 22,23 exceeds even the general Appalachian rate (34%), 15 though no studies offer direct comparisons. Given the paucity of population-based surveys that include questions about sexual orientation, the actual patterns of smoking and tobacco use among rural sexual minorities remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation